2023
DOI: 10.1007/s10546-022-00775-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanisms Associated with the Structure and Evolution of Roll Vortices and Coherent Turbulence in the Hurricane Boundary Layer: A Large Eddy Simulation During the Landfall of Hurricane Harvey

Abstract: Roll vortices are a series of large-scale turbulent eddies that nearly align with the mean wind direction and prevail in the hurricane boundary layer. In this study, the one-way nested WRF-LES model simulation results from Li et al. (J Atmos Sci 78(6):1847–1867, https://doi.org/10.1175/JAS-D-20-0270.1, 2021) are used to examine the structure and generation mechanism of roll vortices and associated coherent turbulence in the hurricane boundary layer during the landfall of Hurricane Harvey from 00 UTC 25 to 18 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…These rolls are generally aligned with the streamlines giving the wave-like appearance. Similar turbulent roll circulations in a TC environment explicitly resolved by LESs have been previously reported by many studies [21,32,56]. To clearly show the vertical structures of the simulated roll circulations by different domains, Figure 6 plots the vertical cross-section of vertical velocity and vertical overturning circulations along the black dashed line indicated in Figure 5.…”
Section: The Rollssupporting
confidence: 73%
“…These rolls are generally aligned with the streamlines giving the wave-like appearance. Similar turbulent roll circulations in a TC environment explicitly resolved by LESs have been previously reported by many studies [21,32,56]. To clearly show the vertical structures of the simulated roll circulations by different domains, Figure 6 plots the vertical cross-section of vertical velocity and vertical overturning circulations along the black dashed line indicated in Figure 5.…”
Section: The Rollssupporting
confidence: 73%
“…The RV intensity was first related to the horizontal divergence in the PBL and then used to quantify the VED contribution from RV. Li and Pu (2023) found that the inflow transports the rolls in the entire storm boundary layer and accumulates near the eyewall to support the intense rolls there. Specifically, in , RV intensity, I w = w′ • w′, is linked to horizontal convergence (negative divergence), where w′ is the vertical component of the RV turbulence.…”
Section: Rv Parameterizationmentioning
confidence: 98%